An integral view of active didactics in the teaching and learning of lean manufacturing - Galarza Cevallos, Marianita
In this article a contextualization of Lean manufacturing is done as a production management model with the objective of reviewing the methodologies used in the teaching - learning process of this tool in the different institutions of higher education (IES) and SENA in the Industrial production technology, Production management and industrial engineering programs, which contribute to the improvement of the productivity and competitiveness of companies, focusing on active teaching with an exercise of Fischertechnik as an integral and practical methodology that allows through the simulation of industrial processes the identification of the changes or losses that occur daily. Through workshops, the diagnosis of the current situation of a process is made and according to the findings or deviations of the different indicators and changes (lost), improvements are proposed based on the application of Lean Manufacturing tools, such as 5 ́S, Smed, VSM, Pokayoke, Kanban, etc. allowing the student to obtain a global and real vision of the different problems and their root causes, generating in it through this didactic active interaction as if they were in real cases in their companies.